2001
DOI: 10.1001/archopht.119.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Enucleation

Abstract: To determine the percent volume replacement by an implant and prosthesis, the long-term sequelae of poor volume replacement, and specific guidelines for volume replacement in pediatric patients. Methods: A retrospective observational study of 16 pediatric patients who underwent enucleation (group 1) and 31 adult patients enucleated in childhood (group 2) was performed. The total volume replacement and the volume replacement by the implant were determined. The incidence of secondary surgical procedures for supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…From the groups analyzed in this study, the control group needed more time for the tissue repair process by applying the conventional treatment. We observed the presence of the conjunctiva were more secretions, peripheral conjunctival tissue exhibited congestion, edema, the allogeneic sclera with a tendency to dissolve(Fig5.a,b), these may be related conjunctival sac contracted became signi cant in the third and sixth postoperative month(P =0.00).Mucous discharge accumulation within the socket causes chronic in ammation and brosis.this idea agrees by Kaltreider and Peake study [30].Due to in ammation, the conjunctival graft shrinks signi cantly, and nally there is a slight conjunctival sac stenosis(Fig 5 .c) .On the other hand, we could observe an effective wound treatment response on patients in the laser group in a short period, in which the rapid vascularization in all the studied cases was visible. At the same time, by contrast-enhanced MRI good vascularization was observed in patients with HA implantation (Fig 2 .g).It was probably associated to LLLT, which contributed to the acceleration of local blood ow.…”
Section: Discussionsupporting
confidence: 86%
“…From the groups analyzed in this study, the control group needed more time for the tissue repair process by applying the conventional treatment. We observed the presence of the conjunctiva were more secretions, peripheral conjunctival tissue exhibited congestion, edema, the allogeneic sclera with a tendency to dissolve(Fig5.a,b), these may be related conjunctival sac contracted became signi cant in the third and sixth postoperative month(P =0.00).Mucous discharge accumulation within the socket causes chronic in ammation and brosis.this idea agrees by Kaltreider and Peake study [30].Due to in ammation, the conjunctival graft shrinks signi cantly, and nally there is a slight conjunctival sac stenosis(Fig 5 .c) .On the other hand, we could observe an effective wound treatment response on patients in the laser group in a short period, in which the rapid vascularization in all the studied cases was visible. At the same time, by contrast-enhanced MRI good vascularization was observed in patients with HA implantation (Fig 2 .g).It was probably associated to LLLT, which contributed to the acceleration of local blood ow.…”
Section: Discussionsupporting
confidence: 86%
“…Enucleation surgery in retinoblastoma patients have an increased complication risk due to adjuvant radio- or chemotherapy in a subset of patients [9]. Furthermore, enucleation at young age may lead to potential volume deficiency problems later in life [1014]. Hence, it is important to primarily select implant materials and surgery techniques that are associated with a low chance of complications and best cosmetic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies point to the importance of adequate volume replacement in the enucleated socket for orbital development and cosmesis in adulthood. 33,34 In fact, Kaltreider et al 35 found that in childhood enucleations, less than 25% of adult-size volume is replaced, and they advocated for the use of the largest implant that a socket can maintain. Even in adults, a smaller implant size may “offer a false sense of security against implant extrusion.” 36 A larger implant in a child may, therefore, provide better orbital size augmentation into adulthood, potentially avoiding the need for a secondary implant exchange in the future.…”
Section: Discussionmentioning
confidence: 99%